Community based maize seed production in the hills and mountains of Nepal: A review - Sapkota, D; Pokhrel, S (Agronomy Journal of Nepal, 2013)
A review on the community based maize seed production and technology dissemination in Nepal was made in 2009 to know the seed production situation and technology dissemination approaches. Twenty three open pollinated maize varieties and one hybrid were released by the Nepal Agricultural Research Council (NARC) up to 2009. A number of stakeholders were involved on improved technologies dissemination, seed production and marketing. Approaches for technology dissemination include district seed self sufficiency program (DISSPRO) and community based seed production (CBSP) program. About 4500 ton of cereal seeds annually has been producing from these approaches. Approach include subsidies on source seeds, creation of revolving funds, group/co-operative formation, their mobilization for participatory varietal selection (PVS), demonstrations, training, informal research and development (IRD) kit distribution and exchange visits. In community level, activities such as community based seed production approaches, particiapatory technology development, verification and dissemination for sustainable seed production and marketing has been taken place. DOI: http://dx.doi.org/10.3126/ajn.v1i0.7550 Agronomy Journal of Nepal (Agron JN) Vol. 1: 2010 pp.107-112